2022
DOI: 10.1007/s00403-022-02497-y
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus after COVID-19 infection and vaccination

Abstract: Lichen planus (LP) is an inflammatory disorder believed to result from CD8 + cytotoxic T -cell (CTL)-mediated autoimmune reactions against basal keratinocytes. We present a review of LP following COVID-19 infection and vaccination. Literature searches were conducted on PubMed and Google Scholar from 2019 to 7/2022. 36 articles were selected based on subject relevance, and references within articles were also screened. 39 cases of post-vaccination LP and 6 cases of post-infection LP were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…However, HCV was not a frequent comorbidity in the current study, as it was present in only four patients. Recently, many case studies have reported an onset of LP after COVID‐19 infection or vaccination 21 . Nevertheless, a general health, comorbidities and immunological status (i.e., factors having an influence on the immune system) of these people have often been insufficiently described, 22 and thus, more studies are needed to confirm the real relationship between LP and COVID‐19 infection or vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…However, HCV was not a frequent comorbidity in the current study, as it was present in only four patients. Recently, many case studies have reported an onset of LP after COVID‐19 infection or vaccination 21 . Nevertheless, a general health, comorbidities and immunological status (i.e., factors having an influence on the immune system) of these people have often been insufficiently described, 22 and thus, more studies are needed to confirm the real relationship between LP and COVID‐19 infection or vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is that the ACE2 receptors on epidermal cells that act as a target for both infection and vaccination are in abundance in the skin and oral mucosa, driving Th1 recruitment and activating the autoimmune cascade that results in lichen planus. Messenger RNA COVID‐19 vaccines are more commonly associated with lichen planus 10,24 …”
Section: Cutaneous Adverse Reactionsmentioning
confidence: 99%
“…However, we acknowledge that comorbidities may remain a confounding factor. In the Discussion section of our review, we also mentioned that immunocompromising comorbidities such as hypertension, diabetes, vitamin D deficiency, and vitiligo may be risk factors that increase susceptibility to LP after COVID-19 infection and vaccination [1]. We further invite the authors to review the clinical generalizability of their reference when discussing comorbidities for lichen planus, as their reference is a case report on dengue after COVID-19 vaccination [2].…”
mentioning
confidence: 99%
“…The authors raised the concern that a layperson's internet post may not guarantee a precise diagnosis. We would like to clarify that all of the references cited in our review were from peer-reviewed studies in which diagnoses of lichen planus were made by qualified healthcare providers through clinical or histopathological findings [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation